Development of Self-Consolidating High Strength Concrete Incorporating Treated Palm Oil Fuel Ash - Alsubari, Belal (Materials (Basel), 2015)
Palm oil fuel ash (POFA) has previously been used as a partial cement replacement in concrete. However, limited research has been undertaken to utilize POFA in high volume in concrete. This paper presents a study on the treatment and utilization of POFA in high volume of up to 50% by weight of cement in self-consolidating high strength concrete (SCHSC). POFA was treated via heat treatment to reduce the content of unburned carbon. Ordinary Portland cement was substituted with 0%, 10%, 20%, 30%, and 50% treated POFA in SCHSC. Tests have been conducted on the fresh properties, such as filling ability, passing ability and segregation resistance, as well as compressive strength, drying shrinkage and acid attack resistance to check the effect of high volume treated POFA on SCHSC. The results revealed that compared to the control concrete mix, the fresh properties, compressive strength, drying shrinkage, and resistance against acid attack have been significantly improved. Conclusively, treated POFA can be used in high volume as a cement replacement to produce SCHSC with an improvement in its properties.